A water-based high-lubricity cutting fluid and preparation method thereof

By combining water-based high-lubricity cutting fluid with lubricating additives and other components, the problem of large amount of water-based cutting fluid and poor cutting quality is solved, and the effects of high lubricity, low friction and low wear are achieved. It is suitable for CNC machine tools and other fields.

CN116751617BActive Publication Date: 2025-02-07DONGGUAN QINZHEN LUBRICATION TECH CO LTD

Patent Information

Application Number
CN202310544038.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2025-02-07
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

During the use of existing water-based cutting fluid, in order to ensure good heat dissipation effect, the use amount is large and the cutting quality is poor. How to improve the lubricity of water-based cutting fluid is an urgent problem that technicians need to solve.

Method used

By combining lubricating additives, triethanolamine, oily corrosion inhibitors, benzotriazoles, surfactants, etc., a water-based high-lubricating cutting fluid with a pH of 8-9 is prepared, in which the sulfurization embedded in the lubricating additives is embedded in the lubricating additives The fatty acid esters are thrown out at high centrifugal speed and adhere to the metal surface to form a dense vulcanized film, which plays a lubricating role.

Benefits of technology

Effectively reduce shear stress, reduce friction and power consumption, reduce temperature and tool wear between the friction parts between the tool and the processed part, improve the cutting performance of the workpiece material, improve the lubricating performance of the cutting fluid, make it small in use and high cutting quality .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004229132290000101
    Figure BDA0004229132290000101
Patent Text Reader

Abstract

The present invention relates to the technical field of cutting fluids, and in particular to a water-based high-lubricity cutting fluid and a preparation method thereof, comprising triethanolamine, an oily corrosion inhibitor, a lubricating additive, benzotriazole, a surfactant, a potassium hydroxide solution, a pH regulator and deionized water. The water-based high-lubricity cutting fluid in the present invention is compounded by lubricating additives, triethanolamine, an oily corrosion inhibitor, benzotriazole, a surfactant and the like, wherein the sulfide fatty acid ester embedded in the lubricating additive is thrown out from the pores under the action of centrifugal force when subjected to a high centrifugal speed, and adheres to the metal surface to form a dense sulfide film, which plays a lubricating role, can effectively reduce shear stress, reduce friction and power consumption, reduce the temperature of the friction part between the tool and the workpiece and the tool wear, improve the cutting performance of the workpiece material, and improve the lubrication performance of the cutting fluid, so that it has the characteristics of small usage and high cutting quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cutting fluids, in particular to a water-based high-lubricity cutting fluid and a preparation method thereof. Background Art

[0002] A lot of heat will be generated in the process of metal cutting, and because the cutting area is concentrated, the temperature of the cutting position can generally reach 800-1200 degrees Celsius. Since the life of the metal is inversely proportional to the 20th power of the temperature, the cutting parts that are in a high temperature environment for a long time will greatly shorten the life of the cutting tool. Therefore, in order to extend the service life of the cutting tool, the heat is mainly dissipated through the cutting fluid and the material of the tool itself is modified, and the heat dissipation of the cutting fluid is currently the most important method; people use cutting fluid to cool and lubricate the cutting position. Commonly used cutting fluids are mainly divided into oil-based cutting fluids and water-based cutting fluids according to their ingredients. Among them, water-based synthetic cutting fluids overcome the problems of traditional soap-based emulsions that are easy to smell in summer, difficult to dilute in winter, and have poor anti-rust effect. They have no adverse effects on lathe paints and are suitable for cutting and grinding of ferrous metals. They have good cooling, cleaning, and rust prevention characteristics, and are non-toxic, odorless, non-corrosive to the human body, non-corrosive to equipment, and non-polluting to the environment.

[0003] For example, the invention patent with the announcement number CN111349504A discloses a water-based cutting fluid and a preparation method thereof, which includes organic alcohol amine, tung oil dimer acid, preservative, benzotriazole, water softener and water. The water-based cutting fluid has excellent lubrication, anti-corrosion and anti-rust effects, is a green and environmentally friendly water-based cutting fluid, has good biodegradability, and is suitable for various grinding machine processing techniques; although the cutting fluid has certain lubrication and anti-rust effects, in actual use, in order to ensure good heat dissipation effect, on the one hand, the amount used is large, and on the other hand, the temperature of the cutting fluid needs to be kept at a low level, but this will bring about the disadvantages of large amount of cutting fluid used and poor cutting quality. Therefore, how to improve the lubricity of water-based cutting fluid is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a water-based high-lubricity cutting fluid and a preparation method thereof. The water-based high-lubricity cutting fluid is compounded by a lubricating additive, triethanolamine, an oily corrosion inhibitor, benzotriazole, a surfactant, etc., wherein the sulfided fatty acid ester embedded in the lubricating additive is thrown out from the pores under the action of centrifugal force when subjected to a high centrifugal speed, and adheres to the metal surface to form a dense sulfide film, which plays a lubricating role, can effectively reduce shear stress, reduce friction and power consumption, reduce the temperature of the friction part between the tool and the workpiece and the tool wear, thereby improving the cutting performance of the workpiece material, improving the lubrication performance of the cutting fluid, and making it have the characteristics of small usage and high cutting quality.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A water-based high-lubricity cutting fluid, wherein the pH value of the high-lubricity cutting fluid is maintained at 8-9, and the high-lubricity cutting fluid comprises triethanolamine, an oily corrosion inhibitor, a lubricating additive, benzotriazole, a surfactant, a potassium hydroxide solution, a pH regulator and deionized water; the weight parts of the raw materials are as follows: 10-14 parts of triethanolamine, 2-6 parts of the oily corrosion inhibitor, 2-6 parts of the lubricating additive, 1-2 parts of benzotriazole, 2-3 parts of the surfactant, 3-5 parts of the potassium hydroxide solution, 0.1-1.0 parts of the pH regulator and 150-200 parts of deionized water.

[0007] As a further preferred embodiment of the present invention, the oily corrosion inhibitor is composed of sodium petroleum sulfonate, barium petroleum sulfonate and zinc naphthenate in a mass ratio of (2-3):1:(3-4);

[0008] The surfactant is any one of Span 80 and alkylphenol polyoxyethylene ether;

[0009] The concentration of the potassium hydroxide solution is 25-30 wt %.

[0010] As a further preferred embodiment of the present invention, the preparation method of the lubricating additive is as follows:

[0011] 1) dissolving polyvinyl pyrrolidone in anhydrous ethanol, then adding composite graphene oxide, and after ultrasonic dispersion for 3-5 hours, removing the composite graphene oxide that is not dispersed in the solution at a speed of 5000-8000 r / min to obtain a precipitate-free liquid, and then adding the liquid to 2-3 times its volume of petroleum ether, and obtaining the pretreated composite graphene oxide after centrifugation and drying;

[0012] 2) Dissolve polyvinyl pyrrolidone in ethylene glycol at 120-130° C. and treat at a constant temperature for 1-2 hours. After cooling to room temperature, add the solution to an autoclave, add ferric chloride ethylene glycol solution and silver nitrate ethylene glycol solution, mix thoroughly, add pretreated composite graphene oxide to form a reaction solution, react at 130-136° C. for 5-8 hours, cool to room temperature after the reaction is completed, and wash the product repeatedly with deionized water and ethanol to obtain a lubricating additive.

[0013] As a further preferred embodiment of the present invention, the usage ratio of polyvinyl pyrrolidone, anhydrous ethanol and composite graphene oxide is (6-10) g: (200-300) mL: (4-7) g;

[0014] The ultrasonic power is 300-400W.

[0015] As a further preferred embodiment of the present invention, the reaction solution contains 0.04-0.06 mol / L silver nitrate, 0.2-0.4 mol / L polyvinyl pyrrolidone, 1.5-2.0×10 -4 mol / L, pretreated composite graphene oxide 10-15g / L.

[0016] As a further preferred embodiment of the present invention, the preparation method of the composite graphene oxide is as follows:

[0017] 1) adding an appropriate amount of graphene oxide to deionized water, ultrasonically dispersing for 1-3 hours under ice bath conditions to obtain a dispersion, then adding the dispersion and ammonia water into a reactor and keeping the temperature for 12-15 hours, freeze-drying the obtained product, and then dispersing and grinding to obtain a three-dimensional porous graphene oxide;

[0018] 2) Add the three-dimensional porous graphene oxide into a vacuum tank, evacuate the tank, spray the sulfidized fatty acid ester on the surface of the three-dimensional porous graphene oxide, and maintain the vacuum degree unchanged. After immersion treatment for 30-60 minutes, slowly release the pressure to normal pressure, take out the product, and obtain composite graphene oxide.

[0019] As a further preferred embodiment of the present invention, the ultrasonic power is 800-1000W;

[0020] The concentration of the dispersion is 5-10 mg / mL.

[0021] As a further preferred embodiment of the present invention, the volume ratio of the dispersion to the aqueous ammonia is (120-140): (25-30);

[0022] The temperature in the reactor is 180-190°C.

[0023] As a further preferred embodiment of the present invention, the ratio of the three-dimensional porous graphene oxide to the sulfurized fatty acid ester is (1-5) g: (50-80) mL;

[0024] The vacuum degree of the vacuum pumping is -0.02--0.05MPa;

[0025] The vacuum tank is in continuous rotation;

[0026] The immersion treatment time is 30-60 minutes.

[0027] A method for preparing a water-based high-lubricity cutting fluid specifically comprises the following steps:

[0028] According to the ratio, triethanolamine, oily corrosion inhibitor, benzotriazole, surfactant and potassium hydroxide solution are added to deionized water in turn, and the lubricating additive is added after being fully stirred and mixed. After being evenly dispersed, the pH adjuster is added, and the pH value is maintained at 8-9 to obtain the required high-lubricity cutting fluid.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] In the present invention, ammonia water is used as a nitrogen source, a hydrothermal reduction method is used, and a graphene oxide with a three-dimensional porous structure is obtained by freeze drying. The formed three-dimensional porous graphene oxide has a rich micro-mesoporous structure, and the pores are interconnected, and has a high porosity. The three-dimensional porous graphene oxide is used as a carrier, and a sulfided fatty acid ester is loaded in the pores of the three-dimensional porous graphene oxide by a vacuum impregnation method. The rich pore structure of the three-dimensional porous graphene oxide is tortuous, which greatly restricts the flow of the sulfided fatty acid ester, so that the sulfided fatty acid ester is confined in the pores. When the sulfided fatty acid ester is subjected to a high centrifugal speed, it is subjected to the action of the centrifugal force and flows out of the pores. The sulfide film is thrown out and attached to the metal surface to form a dense sulfide film, which plays a lubricating role, can effectively reduce shear stress, reduce friction and power consumption, reduce the temperature of the friction part between the tool and the workpiece and the tool wear, thereby improving the cutting performance of the workpiece material, and plays a key role in improving the lubrication performance; and in order to improve the stability of the cutting fluid and avoid the agglomeration and sedimentation of the composite graphene oxide, in the present invention, polyvinyl pyrrolidone is modified on the surface of the graphene oxide by non-covalent bonds, thereby effectively improving the dispersibility of the composite graphene oxide in the water-based cutting fluid, making it less likely to agglomerate and settle, thereby helping to improve the stability of the water-based cutting fluid.

[0031] In order to further improve the solid-restricting effect of the sulfided fatty acid ester and inhibit the overflow of the sulfided fatty acid ester, in the present invention, the pretreated composite graphene oxide is used as the matrix, and the ethylene glycol thermal reduction method is adopted. The ethylene glycol is decomposed into acetaldehyde at a high temperature exceeding 120° C. The acetaldehyde reduces the silver ions into silver atoms. The silver atoms aggregate into single crystals, twins or multiple twins. At a sufficiently high temperature, the crystal nuclei grow to a critical size to form a five-fold twin structure dominated by low-energy crystal planes. By introducing polyvinyl pyrrolidone that can directionally wrap the crystal plane, the silver atoms can be enriched and directionally grow on the crystal plane, thereby forming nanowires with an ultra-high aspect ratio on the surface of the matrix. Since the formed nanowires are long and have a large contact area with each other, they are very easy to be entangled and cross-linked with each other, thereby forming a multi-level network structure, thereby wrapping the pretreated composite graphene oxide, further inhibiting the outflow of the sulfided fatty acid ester, so that the sulfided fatty acid ester will slowly overflow under the condition of high centrifugal speed, and adhere to the metal surface to form a dense sulfide film.

[0032] The water-based high-lubricity cutting fluid of the present invention is compounded by lubricating additives, triethanolamine, oily corrosion inhibitors, benzotriazole, surfactants and the like. The sulfided fatty acid ester embedded in the lubricating additive is thrown out from the pores under the action of centrifugal force when subjected to high centrifugal speed, and adheres to the metal surface to form a dense sulfide film, which plays a lubricating role, can effectively reduce shear stress, reduce friction and power consumption, reduce the temperature of the friction part between the tool and the workpiece and the tool wear, thereby improving the cutting performance of the workpiece material, improving the lubrication performance of the cutting fluid, making it have the characteristics of small usage and high cutting quality, and is widely used in automobile and motorcycle parts processing and other machinery industries, especially suitable for CNC machine tools, machining centers and other fields. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the embodiment of the present invention, the oily corrosion inhibitor is composed of sodium petroleum sulfonate, barium petroleum sulfonate and zinc naphthenate in a mass ratio of 2:1:3; the surfactant is Span 80; and the concentration of the potassium hydroxide solution is 30wt%.

[0035] Example 1

[0036] A water-based high-lubricity cutting fluid, wherein the pH value of the high-lubricity cutting fluid is maintained at 8, comprising the following raw materials in parts by weight: 10 parts of triethanolamine, 2 parts of oily corrosion inhibitor, 2 parts of lubricating additive, 1 part of benzotriazole, 2 parts of surfactant, 3 parts of potassium hydroxide solution, 0.1 part of pH regulator, and 150 parts of deionized water;

[0037] The preparation method of the high lubricity cutting fluid specifically comprises the following steps:

[0038] According to the ratio, triethanolamine, oily corrosion inhibitor, benzotriazole, surfactant and potassium hydroxide solution are added to deionized water in turn, and the lubricating additive is added after being fully stirred and mixed. After being evenly dispersed, the pH adjuster is added and the pH value is maintained at 8 to obtain the required high-lubricity cutting fluid.

[0039] Wherein, the preparation method of lubricating additive is as follows:

[0040] 1) adding an appropriate amount of graphene oxide to deionized water, and dispersing it ultrasonically at 800W for 1 hour under ice bath conditions to obtain a dispersion with a concentration of 5 mg / mL, then measuring 120 mL of the dispersion and adding it to a reactor with 25 mL of ammonia water, heating it to 180° C. and keeping it warm for 12 hours, freeze-drying the obtained product, and then dispersing and grinding it to obtain three-dimensional porous graphene oxide;

[0041] 2) adding 1 g of three-dimensional porous graphene oxide into a vacuum tank, evacuating to a vacuum degree of -0.02 MPa, rotating the vacuum tank continuously, and spraying 50 mL of sulfurized fatty acid ester on the surface of the three-dimensional porous graphene oxide that is constantly rolling, and maintaining the vacuum degree unchanged, after immersion treatment for 30 minutes, slowly releasing the pressure to normal pressure, taking out the product, and obtaining a composite graphene oxide;

[0042] 3) 6 g of polyvinyl pyrrolidone was dissolved in 200 mL of anhydrous ethanol, and then 4 g of composite graphene oxide was added. After ultrasonic dispersion at 300 W for 3 h, the composite graphene oxide that was not dispersed in the solution was removed at a speed of 5000 r / min to obtain a precipitate-free liquid, which was then added to 2 times its volume of petroleum ether, and the pretreated composite graphene oxide was obtained after centrifugation and drying;

[0043] 4) Dissolve polyvinyl pyrrolidone in ethylene glycol at 120°C and keep the temperature constant for 1h. After cooling to room temperature, add the solution to an autoclave, add ferric chloride ethylene glycol solution and silver nitrate ethylene glycol solution, mix thoroughly, and add the pretreated composite graphene oxide to form a reaction solution. The reaction solution contains 0.04 mol / L silver nitrate, 0.2 mol / L polyvinyl pyrrolidone, and 1.5×10 -4mol / L, pre-treated composite graphene oxide 10g / L, reacted at 130°C for 5h, cooled to room temperature after the reaction was completed, and the product was repeatedly washed with deionized water and ethanol to obtain a lubricating additive.

[0044] Example 2

[0045] A water-based high-lubricity cutting fluid, wherein the pH value of the high-lubricity cutting fluid is maintained at 8.5, and comprises the following raw materials in parts by weight: 12 parts of triethanolamine, 5 parts of oily corrosion inhibitor, 5 parts of lubricating additive, 1.5 parts of benzotriazole, 2.5 parts of surfactant, 4 parts of potassium hydroxide solution, 0.5 parts of pH regulator, and 180 parts of deionized water;

[0046] The preparation method of the high lubricity cutting fluid specifically comprises the following steps:

[0047] According to the ratio, triethanolamine, oily corrosion inhibitor, benzotriazole, surfactant and potassium hydroxide solution are added to deionized water in turn, and the lubricating additive is added after being fully stirred and mixed. After being evenly dispersed, the pH adjuster is added and the pH value is maintained at 8.5 to obtain the required high-lubricity cutting fluid.

[0048] Wherein, the preparation method of lubricating additive is as follows:

[0049] 1) adding an appropriate amount of graphene oxide to deionized water, and dispersing it ultrasonically at 900 W for 2 h in an ice bath to obtain a dispersion with a concentration of 8 mg / mL, then measuring 130 mL of the dispersion and adding it to a reactor with 26 mL of ammonia water, heating it to 185° C. and keeping it warm for 13 h, freeze-drying the obtained product and then dispersing and grinding it to obtain three-dimensional porous graphene oxide;

[0050] 2) adding 3 g of three-dimensional porous graphene oxide into a vacuum tank, evacuating to a vacuum degree of -0.03 MPa, rotating the vacuum tank continuously, and spraying 70 mL of sulfurized fatty acid ester on the surface of the three-dimensional porous graphene oxide that is constantly rolling, and maintaining the vacuum degree unchanged, after immersion treatment for 50 min, slowly releasing the pressure to normal pressure, taking out the product, and obtaining a composite graphene oxide;

[0051] 3) 8 g of polyvinyl pyrrolidone was dissolved in 250 mL of anhydrous ethanol, and then 5 g of composite graphene oxide was added. After ultrasonic dispersion at 350 W for 4 h, the composite graphene oxide that was not dispersed in the solution was removed at a speed of 7000 r / min to obtain a precipitate-free liquid, which was then added to 2.5 times its volume of petroleum ether, and the pretreated composite graphene oxide was obtained after centrifugation and drying;

[0052] 4) Dissolve polyvinyl pyrrolidone in ethylene glycol at 125°C and keep the temperature constant for 1.5h. After cooling to room temperature, add the solution to an autoclave, add ferric chloride ethylene glycol solution and silver nitrate ethylene glycol solution, mix thoroughly, and add the pretreated composite graphene oxide to form a reaction solution. The reaction solution contains 0.05mol / L silver nitrate, 0.3mol / L polyvinyl pyrrolidone, and 1.8×10 -4 mol / L, pre-treated composite graphene oxide 12g / L, reacted at 135°C for 6h, cooled to room temperature after the reaction was completed, and the product was repeatedly washed with deionized water and ethanol to obtain a lubricating additive.

[0053] Example 3

[0054] A water-based high-lubricity cutting fluid, wherein the pH value of the high-lubricity cutting fluid is maintained at 8-9, and comprises the following raw materials in parts by weight: 14 parts of triethanolamine, 6 parts of oily corrosion inhibitor, 6 parts of lubricating additive, 2 parts of benzotriazole, 3 parts of surfactant, 5 parts of potassium hydroxide solution, 1 part of pH regulator, and 200 parts of deionized water;

[0055] The preparation method of the high lubricity cutting fluid specifically comprises the following steps:

[0056] According to the ratio, triethanolamine, oily corrosion inhibitor, benzotriazole, surfactant and potassium hydroxide solution are added to deionized water in turn, and the lubricating additive is added after being fully stirred and mixed. After being evenly dispersed, the pH adjuster is added and the pH value is maintained at 9 to obtain the required high-lubricity cutting fluid.

[0057] Wherein, the preparation method of lubricating additive is as follows:

[0058] 1) adding an appropriate amount of graphene oxide to deionized water, and dispersing it ultrasonically at 1000W for 3 hours under ice bath conditions to obtain a dispersion with a concentration of 10 mg / mL, then measuring 140 mL of the dispersion and adding it to a reactor with 30 mL of ammonia water, heating it to 190° C. and keeping it warm for 15 hours, freeze-drying the obtained product and then dispersing and grinding it to obtain three-dimensional porous graphene oxide;

[0059] 2) adding 5 g of three-dimensional porous graphene oxide to a vacuum tank, evacuating to a vacuum degree of -0.05 MPa, continuously rotating the vacuum tank, and spraying 80 mL of sulfurized fatty acid ester on the surface of the three-dimensional porous graphene oxide that is constantly rolling, and maintaining the vacuum degree unchanged, after immersion treatment for 60 min, slowly releasing the pressure to normal pressure, taking out the product, and obtaining a composite graphene oxide;

[0060] 3) dissolving 10 g of polyvinyl pyrrolidone in 300 mL of anhydrous ethanol, then adding 7 g of composite graphene oxide, and ultrasonically dispersing at 400 W for 5 h, removing the composite graphene oxide that is not dispersed in the solution at a speed of 8000 r / min to obtain a precipitate-free liquid, and then adding the liquid to 3 times its volume of petroleum ether, and obtaining a pretreated composite graphene oxide after centrifugation and drying;

[0061] 4) Dissolve polyvinyl pyrrolidone in ethylene glycol at 130°C and keep the temperature constant for 2h. After cooling to room temperature, add the solution to an autoclave, add ferric chloride ethylene glycol solution and silver nitrate ethylene glycol solution, mix thoroughly, and add the pretreated composite graphene oxide to form a reaction solution. The reaction solution contains 0.06 mol / L silver nitrate, 0.4 mol / L polyvinyl pyrrolidone, and 2.0×10 -4 mol / L, pre-treated composite graphene oxide 15g / L, reacted at 136°C for 8h, cooled to room temperature after the reaction was completed, and the product was repeatedly washed with deionized water and ethanol to obtain a lubricating additive.

[0062] Comparative Example 1: This comparative example is substantially the same as Example 1, except that it does not contain a lubricating additive.

[0063] Comparative Example 2: This comparative example is basically the same as Example 1, except that three-dimensional porous graphene oxide is used instead of the lubricating additive.

[0064] Comparative Example 3: This comparative example is basically the same as Example 1, except that composite graphene oxide is used instead of the lubricating additive.

[0065] Comparative Example 4: This comparative example is basically the same as Example 1, except that pretreated composite graphene oxide is used instead of the lubricating additive.

[0066] Comparative Example 5: The water-based cutting fluid disclosed in Example 1 of the invention patent with publication number CN111349504A was used.

[0067] Test experiment:

[0068] The cutting fluid samples provided in Examples 1-3 and Comparative Examples 1-5 were selected to measure the friction coefficient according to SH / T0201-1992 Liquid Lubricant Friction Coefficient Determination Method (Falex Pin and V-Block Method), and the wear area was measured using a REICHERTM2 friction and wear testing machine. The test results are shown in Table 1.

[0069] Table 1

[0070]

[0071]

[0072] It can be seen from Table 1 that the water-based high-lubricity cutting fluid in the present invention has good lubricity, can ensure the surface accuracy and surface finish of the workpiece, and can reduce the wear area of ​​the workpiece and improve the quality of the workpiece.

[0073] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A water-based high lubricity cutting fluid, characterized in that: The pH value of the high lubricity cutting fluid is maintained at 8-9, and the fluid comprises triethanolamine, an oily corrosion inhibitor, a lubricating additive, benzotriazole, a surfactant, a potassium hydroxide solution, a pH regulator, and deionized water; the weight proportions of the raw materials are as follows: 10-14 parts of triethanolamine, 2-6 parts of an oily corrosion inhibitor, 2-6 parts of a lubricating additive, 1-2 parts of benzotriazole, 2-3 parts of a surfactant, 3-5 parts of a potassium hydroxide solution, 0.1-1.0 parts of a pH regulator, and 150-200 parts of deionized water; The preparation method of the lubricating additive is as follows: 1) dissolving polyvinyl pyrrolidone in anhydrous ethanol, then adding composite graphene oxide, and after ultrasonic dispersion for 3-5 hours, removing the composite graphene oxide that is not dispersed in the solution at a speed of 5000-8000 r / min to obtain a precipitate-free liquid, and then adding the liquid to 2-3 times its volume of petroleum ether, and obtaining the pretreated composite graphene oxide after centrifugation and drying; 2) dissolving polyvinyl pyrrolidone in ethylene glycol at 120-130° C. and treating at a constant temperature for 1-2 hours, cooling to room temperature, adding the solution to an autoclave, adding ferric chloride ethylene glycol solution and silver nitrate ethylene glycol solution, mixing thoroughly, adding pretreated composite graphene oxide to form a reaction solution, reacting at 130-136° C. for 5-8 hours, cooling to room temperature after the reaction is completed, and repeatedly washing the product with deionized water and ethanol to obtain a lubricating additive; The preparation method of the composite graphene oxide is as follows: 1) adding an appropriate amount of graphene oxide to deionized water, ultrasonically dispersing for 1-3 hours under ice bath conditions to obtain a dispersion, then adding the dispersion and ammonia water into a reactor and keeping the temperature for 12-15 hours, freeze-drying the obtained product, and then dispersing and grinding to obtain a three-dimensional porous graphene oxide; 2) Add the three-dimensional porous graphene oxide into a vacuum tank, evacuate the tank, spray the sulfidized fatty acid ester on the surface of the three-dimensional porous graphene oxide, and maintain the vacuum degree unchanged. After immersion treatment for 30-60 minutes, slowly release the pressure to normal pressure, take out the product, and obtain composite graphene oxide.

2. A water-based high lubricity cutting fluid according to claim 1, characterized in that: The oily corrosion inhibitor is composed of sodium petroleum sulfonate, barium petroleum sulfonate and zinc naphthenate in a mass ratio of (2-3):1:(3-4); The surfactant is any one of Span 80 and alkylphenol polyoxyethylene ether; The concentration of the potassium hydroxide solution is 25-30 wt %.

3. A water-based high lubricity cutting fluid according to claim 1, characterized in that: The usage ratio of the polyvinyl pyrrolidone, anhydrous ethanol and composite graphene oxide is (6-10) g: (200-300) mL: (4-7) g; The ultrasonic power in the preparation method of the lubricating additive is 300-400W.

4. A water-based high lubricity cutting fluid according to claim 1, characterized in that: In the reaction solution, silver nitrate 0.04-0.06 mol / L, polyvinyl pyrrolidone 0.2-0.4 mol / L, ferric chloride 1.5-2.0×10 -4 mol / L, pretreated composite graphene oxide 10-15g / L.

5. The water-based high lubricity cutting fluid according to claim 1, characterized in that: The ultrasonic power in the preparation method of the composite graphene oxide is 800-1000W; The concentration of the dispersion is 5-10 mg / mL.

6. The water-based high lubricity cutting fluid according to claim 1, characterized in that: The volume ratio of the dispersion to aqueous ammonia is (120-140):(25-30); The temperature in the reactor is 180-190°C.

7. The water-based high lubricity cutting fluid according to claim 1, characterized in that: The three-dimensional porous graphene oxide and the sulfurized fatty acid ester are used in a ratio of (1-5) g: (50-80) mL; The vacuum degree of the vacuum pumping is -0.02--0.05MPa; The vacuum tank is in continuous rotation; The immersion treatment time is 30-60 minutes.

8. A method for preparing a water-based high lubricity cutting fluid according to any one of claims 1 to 7, characterized in that: The specific steps include: According to the ratio, triethanolamine, oily corrosion inhibitor, benzotriazole, surfactant and potassium hydroxide solution are added to deionized water in turn, and the lubricating additive is added after being fully stirred and mixed. After being evenly dispersed, the pH adjuster is added, and the pH value is maintained at 8-9 to obtain the required high-lubricity cutting fluid.

Citation Information

Patent Citations

  • Water-based cutting fluid and preparation method thereof

    CN111349504A

  • Graphene oxide-containing water-based metal cutting fluid and preparation method thereof

    CN106590906A

Cited By

  • Environment-friendly high-lubrication water-based cutting fluid for semiconductor cutting and preparation method of environment-friendly high-lubrication water-based cutting fluid

    CN121471967A

  • High-cleanliness water-based cutting fluid for multi-wire cutting of silicon wafer and preparation method of high-cleanliness water-based cutting fluid

    CN122080993A